АРДЫН ЗАСГИЙН ГАЗРЫН ГАДААД БОДЛОГО: ХӨЛӨНБУЙРЫН БАРГА ХОШУУДТАЙ ХАРИЛЦСАН НЬ - Ё.Довчин,; Л.ОДЗАЯА, (Politology, 2023)
The new the People's government policy towards Hulunbuir's Barga' In this article after the establishment of new Mongolia the government have an special policy towards the Barga of Hulunbuir. In the foreign policy of new government had a special policy to the other Mongols which were separated from mainland Mongolia. Main goal of it was reunification of the rest mongolia which was proclaimed since the restoration of all mongolia in 1911. The new government have ontinued that policy which was stopped during the previous government by Russia and China pressure. Such archive materials I found and described in this article in case of the policy towards the Barga of HULUNBUIR and will agree if they will reunited.